Analisis Pengaruh Pengetahuan K3 terhadap Perilaku Pekerja Konstruksi ( Studi Kasus : Proyek Preservasi Jalan dan Jembatan Ruas Jalan Perintis Kota Makassar ) - Rizki Ayu Saraswati; Wudi Darul Putra (Journal on Education, 2023)
Inadequate Work Safety Standards and the still high number of work accidents in Indonesia, are evidence of weak attention to the importance of K3 aspects in a construction work. This is motivated by the discrepancy between the understanding of Occupational Safety and Health (K3) knowledge and the application of construction worker behavior, especially in the Makassar City Pioneer Road and Bridge Preservation Project. The assumption of the use of tribute safety which is always underestimated is the cause of the above problems, so it requires direction and guidance on mechanisms, management systems and risks borne by the importance of Occupational Safety and Health. The research method used is regression and correlation analysis, where the regression equation describes the functional relationship to the variables studied. The results showed that there was a high positive correlation relationship between K3 knowledge and work behavior with a correlation value of 0.608 with a range of interpretation of the value coefficient between 0.600 – 0.799. As well as the coefficient of determination (Adjusted r square) of 0.366 or 33.6% of the variables reviewed, which means that 66.4% is influenced by other variables.